Green, simple and large scale synthesis of N-doped graphene quantum dots with uniform edge groups by electrochemical bottom-up synthesis. Issue 86 (31st August 2016) - Tian, Linfan; Yang, Siwei; Yang, Yucheng; Li, Jipeng; Deng, Yuan; Tian, Suyun; He, Peng; Ding, Guqiao; Xie, Xiaoming; Wang, Zhongyang
Abstract : An electrochemical bottom-up synthesis of N-doped GQDs (N-GQDs) with large amount of well-defined edge groups was developed for the first time. The exclusive edge group of the obtained N-GQDs is –NH2 results in the excitation wavelength independence behavior. Abstract : We developed an electrochemical bottom-up synthesis of N-doped GQDs (N-GQDs) with a large number of well-defined edge groups for the first time. This progress is green (both atom utilization and yield are higher than 95%, without by-products), simple and suitable for large scale synthesis (10 g per batch). The exclusive edge group of the obtained N-GQDs is –NH2 because of the amino oxidative coupling of o -phenylenediamine, which results in unique excitation wavelength independence behavior. The high quantum yield ( ϕ = 0.71) of yellow green PL is believed to originate from the localized π state due to the graphitic doping of nitrogen. The edge groups have little influence on the spectral resolved PL lifetime as well as the size distribution. The low biotoxicity of N-GQDs is also proved by live cell fluorescent imaging.